Learning Adobe Dreamweaver CS5.5 - Anderson, Andy (InfiniteSkills, 2011)
"Dreamweaver CS5.5 is an incremental update to the popular web publishing software from Adobe. In this video tutorial, the extremely popular and knowledgeable Andy Anderson introduces you to the latest offering from Adobe, Dreamweaver CS5.5. Andy starts by reviewing the new features in version CS5.5. Covering jQuery Mobile, Multi-screen Authoring, the Browser Lab, CSS Enhancements and more, you will be fully abreast of the new features available to you. Continuing on with the basics of mapping out your project, you will quickly move into learning the interface of Dreamweaver CS5.5, the basics of setting up a site, a document, and working with things like text and images and forms to create amazing web pages. Once you have the hang of the basics, Andy takes this video based training course to the next level, with teaching you the basics of CSS within Dreamweaver CS5.5. Finally, you will move on to FTPing your site to your hosting company, managing and creating templates, snippets, libraries, and so much more. By the conclusion of this computer based training video, you will be well versed in how to use the powerful Adobe Dreamweaver CS5.5 to create and manage your own websites. This tutorial comes complete with extensive working files, to allow you to learn Dreamweaver at your own pace."--Resource description page.